Engineering layered double hydroxide-based sonocatalysts for enhanced sonodynamic-immunotherapy. (April 2023) - Wang, Li; Mao, Zhuo; Wu, Jie; Cui, Xiaoliang; Wang, Yuanjie; Yang, Nailin; Ge, Jun; Lei, Huali; Han, Zhihui; Tang, Wei; Guan, Shanyue; Cheng, Liang
Abstract: Sonodynamic therapy (SDT) highly depends on O2 activation to generate desired reactive oxygen species (ROS), however, the deficiencies of sonocatalysts and the hypoxia tumor microenvironment (TME) limit the treatment effect. Herein, a local element rearrangement strategy is used to reconstruct Fe-based layered double hydroxide (LDH) nanosheets via substituting portions of Mg with Mn element (denoted as MMF NSs) for the first time as novel sonocatalysts for high performance SDT of cancer. The Mn substitution could tune the bond length of Fe-O to activate H2 O2 for improving O2 generation yield, as well as decrease the band gap for promoting separation of excited electrons-holes and prolong the lifetime of electron-hole under ultrasound irradiation. Besides, the MMF NSs could immunostimulatory modulate TME including the ratio of M1 macrophage to M2 subtype and promote the maturation of dendritic cells (DCs) to reinforce high-efficient breast cancer therapy. Consequently, this study highlights novel LDH-based sonocatalysts constructed by a local element rearrangement strategy for improving the SDT-enhanced immunotherapy. Graphical Abstract: A local element rearrangement strategy for MgMnFe-LDH nanosheets (MMF NSs) synthesis for efficient SCT combined with immunotherapy. ga1 Highlights: A local element rearrangement strategy was used to reconstruct Fe-based layered double hydroxide (LDH) nanosheets. Mn substitution could tune the bond length of Fe-O to activate H2 O2 for improving O2 generation yield. Mn substitution could decrease the band gap and prolong the lifetime of electron-hole under US irradiation. MMF NSs could immunostimulatory modulate TME and promote the maturation of dendritic cells (DCs) to reinforce cancer therapy. This study highlights novel LDH-based sonocatalysts for improving the SDT-enhanced immunotherapy.